Analisis Pengaruh Profitabilitas, Likuiditas dan Ukuran Perusahaan Terhadap Nilai Perusahaan Sub Sektor Pariwisata Tahun 2020-2024 - Wijayadi, Pandu; Imronudin, Imronudin (Community Engagement and Emergence Journal (CEEJ), 2025)
This study aims to analyze the influence of profitability, liquidity, and company size on firm value in tourism sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The background of this study is based on the importance of firm value as a key indicator in attracting investor interest and reflecting a company's performance and future prospects. This study uses a quantitative approach with panel data regression analysis and the selection of the Random Effects Model (REM). The sample used was 18 companies, with a total of 90 observational data obtained from annual financial reports. The results show that profitability has a negative but insignificant effect on firm value. Liquidity has a positive but also insignificant effect on firm value. Meanwhile, firm size has a negative and significant effect on firm value. These findings imply that large company size does not always reflect high value, especially in the context of the post-pandemic tourism industry. This study is expected to serve as a reference for financial managers and investors in evaluating factors influencing firm value in the tourism sector.